Clinico-epidemiological profile of palmoplantar dermatoses in northeast India - S., Sana; Devi, Bijayanti; S., Mrudula (International Journal of Research in Dermatology, 2021)
Background: Palmoplantar dermatoses are skin diseases affecting palms and soles and are commonly seen in the dermatology practice. It can cause significant discomfort to the patients, affecting their daily activities and also is a diagnostic dilemma to the physician. The aim of this study is to determine the clinico-epidemiological profile of palmoplantar dermatoses among patients attending the outpatient department (OPD). Methods: Hospital based cross sectional study carried out from September 2018 to August 2020 in patients attending outpatient department of dermatology in Regional Institute of Medical Sciences (RIMS) Hospital, Imphal, Manipur. Results: Of the total 200 patients, nearly half were males (50.5%). Most common age group involved was 26-45 years. Itching was the most common symptom (60%). Multiple lesions with palm alone involvement accounted for higher percentage with 39.5% followed by palmoplantar involvement. Most common palmoplantar dermatosis in the study was eczema with 23% followed by psoriasis (7.5%), dermatophytosis (7%), verruca vulgaris (6.5%), and keratolysis exfoliativa (6%). Conclusions: Eczema was the most common palmoplantar disorder followed by psoriasis. Diagnosis of palmoplantar dermatoses is important at the earliest for appropriate management which helps in improving the patient’s quality of life.